2015
DOI: 10.1021/acs.chemmater.5b00314
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lithium-Ion Energy Storage Utilizing the Surface Redox Reactions in Folded Graphene Films

Abstract: Reduced graphene oxides are active as positive electrodes for lithium-ion energy storage based on the surface redox reactions between oxygen functional groups and Li ions. For effective Li-ion energy storage within a confined mass and volume, free-standing, high-packing density, and redox-active graphene films were fabricated by a simple two-step compression and vacuum-drying process from a hydrothermally reduced graphene hydrogel. The assembled graphene films showed a folded microstructure with high packing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
129
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 78 publications
(145 citation statements)
references
References 60 publications
16
129
0
Order By: Relevance
“…[168] They also showed that the RGO electrodes can deliver a high capacity of ≈160 mA h g −1 based on the redox reactions of the oxygen functional groups with Liions with exceptional cycling stability up to 50 000 charge and discharge cycles. [168] They also showed that the RGO electrodes can deliver a high capacity of ≈160 mA h g −1 based on the redox reactions of the oxygen functional groups with Liions with exceptional cycling stability up to 50 000 charge and discharge cycles.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
See 4 more Smart Citations
“…[168] They also showed that the RGO electrodes can deliver a high capacity of ≈160 mA h g −1 based on the redox reactions of the oxygen functional groups with Liions with exceptional cycling stability up to 50 000 charge and discharge cycles. [168] They also showed that the RGO electrodes can deliver a high capacity of ≈160 mA h g −1 based on the redox reactions of the oxygen functional groups with Liions with exceptional cycling stability up to 50 000 charge and discharge cycles.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…[165] They also showed that the capacity of pristine CNT (26 mA h g −1 ) can be significantly increased to 118 mA h g −1 as increasing the amount of the oxygen functional groups on CNT. [100,[167][168][169][170][171][172][173][174][175] Chen et al demonstrated that partially oxidized graphene can facilitate the penetration of aqueous electrolyte and induced the pseudocapacitive effects (Figure 18a). [100,[167][168][169][170][171][172][173][174][175] Chen et al demonstrated that partially oxidized graphene can facilitate the penetration of aqueous electrolyte and induced the pseudocapacitive effects (Figure 18a).…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
See 3 more Smart Citations